Artificial Intelligence and the Management of Stock Corporations – Organisational and Liability-Related Issues - Jung, Peter (Pázmány Law Review, 2025)
Even if self-driving corporations are not yet on the horizon, some management tasks may be already performed by Artificial Intelligence (AI). This first raises the question to what extent and under which conditions the deployment of AI in the course of management of a corporation is already possible and can prove useful (I.). Secondly, the question arises whether and under which conditions the directors and the corporation can be held liable for the unlawful use of automated systems and any resulting damage (II.). The following article seeks to answer these questions mainly from the perspective of German and Swiss stock corporation law.